Valuation of Child Health‐Related Quality of Life in the United States. (28th April 2015) - Craig, Benjamin M.; Greiner, Wolfgang; Brown, Derek S.; Reeve, Bryce B.
Abstract: Many economic analyses fail to incorporate evidence on child health‐related quality of life because of a paucity of quality‐adjusted life year (QALY) estimates. This health valuation study is the first to summarize the EQ‐5D‐Y on a QALY scale. Drawn from a nationally representative panel, 5207 adult respondents were asked to choose between two losses in child health‐related quality of life. Based on their choices, a 1‐year increase in child pain/discomfort from 'some' to 'a lot' equals a loss of 4 QALYs (95% CI, 3.8–4.4). Likewise, a 1‐year increase in child anxiety/depression from 'a bit' to 'very worried, sad, or unhappy' equals a loss of 2 QALYs (95% CI, 1.9–2.2). These findings enable the integration of child‐reported outcomes with adult preferences to inform economic analysis. Results inform both clinical practice and resource allocation decisions by enhancing understanding of difficult tradeoffs in child‐reported outcomes. Copyright © 2015 John Wiley & Sons, Ltd.